Studying Management Issue Faced by Malaysian Airlines System Sdn. Bhd. - Wai, Kang Kok; Kee, Daisy Mui Hung; Yong, Lau King; Yi, Lim Jing; Wey, Leong Chi; Alqabandi, Nouf Khalid (Asia Pacific Journal of Management and Education (APJME), 2019)
In facing the challenging business world, including in the aviation industry, Malaysian Airlines System Sdn. Bhd. had come through the ups and downs of the turbulence economy, since 1st May 1947. For the last few years, Malaysian Airlines System Sdn. Bhd. had faced a lot of challenges in managements, operations and financial problems. Our research findings will be focused on the management issue faced by Malaysian Airlines System Sdn. Bhd. and suggesting the best solution academically for this company. Moreover, our research reflects that even the management problem had been solved, there are still several uncontrollable external issues that will haunt the company such as the financial uncertainties. Not to mention that the performance will be greatly affected by the foreign exchange and laws implementation by foreign countries because Malaysia Airlines operates in other countries too. Lastly, our research reflects that if the management problems had been solved, their performance should be better in terms of daily operation management and financial management.